STRATEGI FUNDRAISING ZAKAT PROFESI (STUDI KASUS BAITUL MAAL HIDAYATULLAH PONOROGO) - fikri iskandar fatkhurohman (Journal of Islamic Economics and Philanthropy, 2022)
Zakat as a pillar of Islam has a very important role because it has two dimensions, namely vertical as a form of obedience and obedience to Allah SWT, and a dimension of caring for fellow humans as servants.Zakat is divided into two, namely zakat fitrah and zakat maal. Zakat mal is divided into several types of zakat, including business zakat, agricultural products, livestock, gold, silver, minerals and found items.Seeing the importance of zakat, there must be a good manager in it. LAZNAS Baitul maal hidayatullah ponorogo is a national amil zakat institution which is engaged in the collection of zakat funds, which is found in almost every city in Indonesia.Because many amil zakat institutions, especially those in Ponorogo district, demand the Baitul maal hidayatullah ponorogo amil zakat institution to continue to improve the quality and professionalization as a good institution of competence and professionalism in collecting professional zakat funds.The purpose of this study is to determine the strategy of professional zakat fundraising in Baitul maal hidayatullah ponorogo.This research method is to use a qualitative method using a case study approach.The results of this study The strategy carried out by baitul maal hidayatullah ponorogo uses direct and indirect strategies,the strategy carried out by Baitul Maal Hidayatullah directly by using education to the community in Ponorogo is door to door and through social media.It is proven to be successful where the professional zakat funds collected have increased every year.